2014
DOI: 10.1159/000355791
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity in Chronic Kidney Disease: a Plausible Approach to Vascular Calcification?

Abstract: Vascular calcification (VC) is a prominent feature that affects up to 40 to 80% of Chronic Kidney Disease (CKD) patients depending on the degree of renal impairment. Though etiology and pathogenesis of the different types of VC are far from being elucidated, it is conceivable that an imbalance between promoters and inhibitors represents the condition that triggers VC deposition and progression. In addition to traditional cardiovascular risk factors, several lines of evidence suggest that specific factors may a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Several epidemiological studies have shown that AAC is associated with incident coronary heart disease [ 20 ], myocardial infarction [ 21 ] and stroke [ 22 ]. A more holistic risk mitigation approach, encompassing lifestyle modification or PA, may serve as a credible strategy for diminishing the deposition and advancement of VC [ 23 ]. Nonetheless, a substantial prospective study involving healthy populations revealed a counterintuitive finding: elevated levels of PA were linked to a heightened prevalence and accelerated progression of coronary artery calcium (CAC) [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several epidemiological studies have shown that AAC is associated with incident coronary heart disease [ 20 ], myocardial infarction [ 21 ] and stroke [ 22 ]. A more holistic risk mitigation approach, encompassing lifestyle modification or PA, may serve as a credible strategy for diminishing the deposition and advancement of VC [ 23 ]. Nonetheless, a substantial prospective study involving healthy populations revealed a counterintuitive finding: elevated levels of PA were linked to a heightened prevalence and accelerated progression of coronary artery calcium (CAC) [ 24 ].…”
Section: Introductionmentioning
confidence: 99%